Precision agriculture technology for crop farming - Zhang, Qin, 1956- (CRC Press, 2016)
Precision agriculture technology, when properly integrated into the crop production process, can greatly improve overall production and sustainability. Precision Agriculture Technology for Crop Farming focuses on the technology of site-specific crop management; detailing applications for sensing, data handling, modeling, and control. Written by experts who have contributed significantly to the development of precision agriculture technology, this book reviews its history--establishing background on the various processes and applications--describes the current status, and offers insight into the future technology of precision agriculture.